1999
DOI: 10.1097/00001756-199906030-00014
|View full text |Cite
|
Sign up to set email alerts
|

The role of cholesterol in the biosynthesis of β-amyloid.

Abstract: Addition of the beta-hydroxy-beta-methylglutaryl-CoA (HmG-CoA) reductase inhibitor lovastatin to human HEK cells transfected with the amyloid precursor protein (APP) reduces intracellular cholesterol/protein ratios by 50%, and markedly inhibits beta-secretase cleavage of newly-synthesized APP. Exogenous water-solubilized cholesterol at 200 microg/ml concentration increases newly synthesized beta-amyloidogenic products four-fold. These intracellular changes are detectable by immunoprecipitation and immunofluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
206
0
3

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(219 citation statements)
references
References 8 publications
10
206
0
3
Order By: Relevance
“…SFV protein uptake by almost all neurons was found in both groups. These results corroborate previous findings (36) that cholesterol-dependent A␤ production does not depend on the use of SFV systems.…”
Section: Resultssupporting
confidence: 92%
“…SFV protein uptake by almost all neurons was found in both groups. These results corroborate previous findings (36) that cholesterol-dependent A␤ production does not depend on the use of SFV systems.…”
Section: Resultssupporting
confidence: 92%
“…A␤ production is sensitive to cellular cholesterol levels in vitro and in vivo (34,35,54). To define the enzymatic requirements of cholesterol-dependent A␤ production we applied a set of APP and truncated APP constructs designed to reveal consecutive and independent activities of ␤-and ␥-secretase with modulated cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
“…BACE I has been shown to recycle between the TGN and the plasma membrane via endosomes (72), and cyclodextrin is known to reduce endocytosis (73). Therefore, the observed ␤-secretase inhibition may be due to inhibited endocytosis, whereas normal secretion remains intact (34,35,54), leaving BACE at the plasma membrane, a compartment of unfavorable pH for ␤-secretase cleavage. However, Kalvodova et al (39) showed that BACE activity is sensitive to cholesterol levels even in the absence of trafficking in vitro, which may indicate that removal of cholesterol from the membrane microenvironment of BACE I in the late secretory pathway may suffice to reduce its activity.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies using immortalized and primary cell lines [83][84][85] have demonstrated that increased cholesterol levels can increase the activity of the ␤-secretase pathway, leading to an accumulation of A␤ and A␤ 1-42 peptides, with a resulting increase in formation of extracellular amyloid deposits. Moreover, it has recently been demonstrated that cholesterol is capable of modulating the production of mature glycosylated APP.…”
Section: Cholesterol Homeostasis In Neurodegenerative Conditionsmentioning
confidence: 99%